Deset let od úispesného zavedení prvé monoklonální protilátky (rituximab) do lécby lymfomů - Trnený, M; Klener, P (Casopis lekaru ceskych, 2007)
Cancer treatment is based on combination of systemic chemotherapy and radiotherapy. The new methods of therapy based on biological priniciples have been introduced within last decade. The monoclonal antibody rituximab was launched ten years ago in 1997. This antibody against CD20 antigen, which is expressed on B cell lymphocytes and on the majority of B-cell lymphoid malignancies, has revolutionized the lymphoma therapeutic strategy. The immuno-chemotherapy has dramatically improved the outcome of diffuse large B-cell lymphomas patients. The combination of rituximab and chemotherapy as first line therapy has for the first time improved the survival of follicular lymphoma patients previously considered to be incurable. Rituximab has become the inevitable part of therapeutic regimens for other B-cell lymphomas, chronic lymphocytic leukaemia as well as for some non-malignant diseases. The important milestones, the therapeutic results of rituximab and other approved monoclonal antibodies (alemtuzumab, ibritumomab tiuxetan 90Y) is reviewed in this paper as well as short compendium of new antibodies is given. The cost effectiveness of the new therapy is discussed.
Keywords: Antibodies, Monoclonal, Murine-Derived; lymfom; Antibodies, Neoplasm; alemtuzumab; Humans; protilátky nádorové; radioimunoterapie; radioizotopy ytria; Antibodies, Monoclonal; Lymphoma; lidé; humanizované monoklonální protilátky; Radioimmunotherapy; myší monoklonální protilátky; Antibodies, Monoclonal, Humanized; rituximab; Yttrium Radioisotopes; monoklonální protilátky; Rituximab; Alemtuzumab